KEBIJAKAN KRIMINAL TERHADAP TINDAK PIDANA POLIGAMI DIKAITKAN DENGAN SISTEM HUKUM PERKAWINAN INDONESIA - Sudibyo, Ateng (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
Law No. 1 of 1974 on Marriage basically adhere to the principle of monogamy. Although not essential to the principle of monogamy, there is still a polygamist who often take shortcuts to legalize polygynous marriage. Polygamous marriage act is a violation of Law No. 1 Year 1974 on Marriage, and Government Regulation No. 9 of 1975 on implementation of Law No. 1 Year 1974 on Marriage, although the threat of criminal sanction only published in the Government Regulation. Another case in the Criminal Code (KUHP), the sanction of polygamy as criminal action regulated in Article 279. Is the threat of criminal sanctions contained in the Criminal Code and Regulation No. 9 of 1975 in line with the values and ideals of community law in Indonesia? The purpose of this study is to determine the applicative policy for polygamy as criminal offense in marriages in Indonesiaâ€™s legal system and to formulate the concept of criminalisation policy for polygamous marriage act as criminal offense in the Indonesiaâ€™s legal system of marriage for the future. This is due to criminal sanctions in Article 279 of the Criminal Code and Law No. 1 of 1974 and Article 45 of Government Regulation Number 9 Year 1975, there is still a legal synchrony. The concept of future criminal polygamy criminal policies should apply the principle of ultimum remedium otherwise known as the â€œlast drugâ€. Whatever the reason for the imposition of criminal punishment will still have a negative effect on the perpetrator and his family and will cause sociological and psychological implications if criminal sanctions are applied. In the legal state of Pancasila especially for the Muslims, the concept of marriage is a worship then it must be fostered, if there are deviations should not be destroyed by a criminal threat. Therefore, to overcome the criminal act of polygamy the need of a non penal criminal policy means, that is prevention without punishment.